Air Traffic Smoothness as a Universal Measure for Air Traffic Quality Assessment. (2016) - Dmochowski, Piotr Andrzej; Skorupski, Jacek
Abstract: Air traffic in European airspace is coordinated centrally by the air traffic flow management services – Network Management Operation Centre (NMOC). Their main task is to compare resources (number and capacity of air traffic control sectors) and needs (size of the planned and actual traffic). If it is found that the planned traffic exceeds the capacity of available airspace, corrective actions should be carried out. They consist in changing the takeoff time, or changing aircraft routes so as to avoid congested sectors or even cancelling the flight. Unfortunately, determining only the traffic volume is not sufficient to identify the needs, because very important are also: aircraft trajectories, manoeuvres performed, types of aircraft, their speed and other restrictions. Indeed, these factors determine the possibility to control the traffic by air traffic controllers. This makes it necessary to seek another indicator characterizing the traffic that must be handled. The paper proposes to use the notion of air traffic smoothness as a new, universal measure for characterizing the quality of air traffic. It can also serve as a measure of the traffic volume in the control sector or even as a traffic safety measure. The concept of smoothness is easier to use than the notion of the traffic complexity, which is increasingly being used, e.g. in the assessment of the capacity of the sector. The paper presents a new method for determining the air traffic smoothness, which uses both flight plans, their current implementation and the so-called favourable flight plans. On the basis of the measured data it is shown how to calculate the traffic smoothness for selected sectors. Indicating directions of further planned research, calculations were made to determine the relationship between the air traffic smoothness and its volume, which in turn may allow the use of the concept of smoothness to determine the capacity of control sectors and supporting air traffic flow management services.